Korelasi Pola Asuh Orang Tua dengan Minat Belajar Anak Usia Sekolah Dasar di Exellent Course - Lusiani Rahmadanti; Fina Fakhriyah; Deka Satiawan (STKIP Andi Matappa Pangkep, 2021)
This study aims to determine the relationship between parenting styles and interest in learning elementary school age children in the Excellent Course. This research was carried out at the Excellent Course in November of the 2020/2021 academic year. This research is a quantitative research using correlation method with parenting style variable as independent variable and children's learning interest as dependent variable. Sampling was done using a saturated sampling technique where all members of the population were used as samples. The number of samples in this study were 20 children. Data collection using questionnaires and interviews. Data analysis used Pearson product moment correlation test. In the correlation test, the correlation coefficient is -1.9656 with of 2.101. Then is -1.9656 <2.101. This shows that there is no significant relationship between parenting styles and interest in learning for elementary school age children in the Excellent Course.